Design and Use of a High‐Pressure Stirred IR Cell for Operando Studies in Homogeneous Catalysis. Issue 9 (18th August 2021) - Crotti, Corrado; Ferretti, Francesco; Ragaini, Fabio
Abstract: The design and operation of a new kind of high pressure/high temperature stirred IR cell is described. The cell is a stand‐alone autoclave made of Hastelloy and effective stirring and gas diffusion are provided by a magnetically driven Teflon shaft. The length of the optical path can be regulated without the need of calibrated spacers and the problem of the sealing of the windows to the cell body has been solved by employing FEP (fluorinated ethylene propylene) encapsulated Viton O‐rings, which, upon adapting to the cell when warmed, provide an excellent seal that is also tolerant of all standard solvents. The use of this kind of O‐rings allows taking advantage of the chemical resistance of Teflon without needing to mechanically stress the fragile windows as it would be required if bulk Teflon O‐rings were employed. Abstract : A new type of integrated autoclave/high pressure‐high temperature IR cell is described, that may also be adapted to UV‐Vis spectroscopic studies. The sealing of the windows to the cell body is achieved by the use of fluoro ethylene propylene (FEP) encapsulated Viton O‐rings, which allow exposing to the solution a material with chemical properties similar to those of Teflon, without requiring the windows to be subject to a strong mechanical stress, as it is the case when bulk Teflon O‐rings are employed.